Peran Mediasi Kepuasan Pelanggan pada Pengaruh Keterikatan Emosi terhadap Loyalitas Pelanggan Rolag Kopi Kayoon Surabaya - Lintang Lilla Lilla Maulidina; Sanaji Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This study aims to analyze the effect of emotional attachment on customer loyalty through customer satisfaction as a mediating variable. This research uses quantitative methods, nonprobability sampling, the sampling method used was purposive sampling and the sample in this study was 200 respondents. The data were analyzed using path analysis. The results of this study are that there is a positive influence of emotional attachment on customer satisfaction and there is a positive effect of customer satisfaction on customer loyalty at Rolag Kopi Kayoon Surabaya.